The relationship between leadership styles and job performance under the Chinese culture at Jiahe Beer Corporation in hebei province China [electronic resource] - Xue, Xiong Fei, 1986- (2010)
Thesis (Sarjana Sains (Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2010